2013
DOI: 10.1002/eji.201343512
|View full text |Cite
|
Sign up to set email alerts
|

Role of IL‐10‐producing regulatory B cells in control of cerebral malaria in Plasmodium berghei infected mice

Abstract: IntroductionMalaria caused by infection with protozoan parasites of Plasmodium spp. is one of the most serious infectious diseases of humans and causes about one million deaths annually. Plasmodium infection may induce multiple disease syndromes including severe anemia, metabolic acidosis, and neurological dysfunction, e.g. cerebral malaria (CM) [1]. Sequestration of the Correspondence: Dr. Zhong Su e-mail: su_zhong@gibh.ac.cn parasitized red blood cells (pRBCs) in brain microvessels is a characteristic histop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 37 publications
2
40
0
Order By: Relevance
“…Adoptive transfer of IL-10 + B regs to P. berghei infected mice significantly reduced the accumulation of NK and CD8 + T cells and hemorrhage in brain tissue, and improved the survival of the mice compared with control groups without altering parasitemia. Treatment of B reg-cell recipient mice with anti-IL-10 receptor mAb blocked the protective effect of B reg cells [79]. As B regs can contribute to regulation of inflammation and prevent immunopathology, they may also suppress protective host responses and increase susceptibility for infections.…”
Section: Regulatory B Cells In Infectionsmentioning
confidence: 96%
“…Adoptive transfer of IL-10 + B regs to P. berghei infected mice significantly reduced the accumulation of NK and CD8 + T cells and hemorrhage in brain tissue, and improved the survival of the mice compared with control groups without altering parasitemia. Treatment of B reg-cell recipient mice with anti-IL-10 receptor mAb blocked the protective effect of B reg cells [79]. As B regs can contribute to regulation of inflammation and prevent immunopathology, they may also suppress protective host responses and increase susceptibility for infections.…”
Section: Regulatory B Cells In Infectionsmentioning
confidence: 96%
“…It has been demonstrated that Bregs were capable of suppressing the proliferation of CD4 +   CD25 −   T cells [31] and production of interferon gamma (IFN- γ ) and IL-17 by Th1 and T helper 17 (Th17) cells, respectively [32, 33]. In vitro studies in human had further postulated the potential ability of Breg cells to influence innate immunity by abrogating mitogen-stimulated secretion of TNF- α by monocytes, macrophages, and T cells.…”
Section: Characteristics Of Regulatory B Cellsmentioning
confidence: 99%
“…As such, IL-27 plays a dual role as it suppresses efficient parasitemia control in primary and secondary infections, while it also protects against severe inflammatory liver pathology (Findlay et al 2010;Gwyer et al 2014), illustrating the importance of this cytokine in steering the immunological balance of malaria toward equilibrium or imbalances. Besides T cells, regulatory B cells also produce IL-10 in murine malaria and may contribute to the suppression of CM (Liu et al 2013). With P. vivax also CD14 hi CD16/Fcγ RIIIA + 'inflammatory' monocytes seem to be a source of IL-10 production, which is produced in combination with TNF (Antonelli et al 2014).…”
Section: Regulatory T Cellsmentioning
confidence: 99%